Making the Case: Intra-arterial Therapy for Less Common Metastases - Gordon, Andrew C.; Uddin, Omar M.; Riaz, Ahsun; Salem, Riad; Lewandowski, Robert J. (Seminars in Interventional Radiology, 2017)
Intra-arterial therapies have high antitumor activity for both primary and secondary hepatic malignancies. Selective infusions allow increased delivery of cytoreductive therapy to the tumor bed while sparing the normal hepatic parenchyma. These therapies are now often applied in the outpatient setting or with short overnight hospital stays and have a growing role in the treatment of liver-dominant disease from metastatic colorectal cancer and from neuroendocrine tumors. Less commonly, intra-arterial therapies are applied to treat secondary hepatic malignancies from breast cancer, melanoma, pancreatic adenocarcinoma, and soft-tissue sarcomas. The available data are limited and generally retrospective observational cohort series of single institutions. The purpose of this article is to summarize the recent literature on outcomes for intra-arterial therapy in nonsurgical patients. Multi-institutional registries and prospective data are greatly needed, as intra-arterial therapies are increasingly applied in these patients to stop progression of chemorefractory tumors.
Keywords: hepatic artery infusion chemotherapy; chemoembolization; radioembolization; liver metastases; interventional radiology